Nuwe Testament tekste en kontekste: Oor die verband tussen hermeneutiek, identiteite en gemeenskappe - Punt, Jeremy (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
New Testament texts and contexts: On the relationship between hermeneutics, identities, and communities This paper focuses on different texts, Pauline texts as well as those (scriptural) texts invoked by Paul in his texts, and ever-present imperial “super”-texts. The imperial co-establishes the social setting of Paul’s letters given the rhetorical use of Othering in the Roman Empire with its identity politics. The rhetorical power of Paul and his scriptural texts contributed to discursive formations, since a strong sense of being and identity was negotiated through these texts, even when admitting that such formations are always in process, mutating and reformatting. Construing notions of Others was a particularly important feature in defining boundaries, for generating insiders and outsiders in Pauline texts.